Healing through social media motivational content among Gen Z / Chee Jia Xi and Maizurah Khathu Abdul Hamid - Chee, Jia Xi; Abdul Hamid, Maizurah Khathu (Faculty of Communication and Media Studies (FCMS), 2024)
Social media has become a pivotal communication platform in the digital age, where individuals—especially Generation Z (born 1997-2012)—actively engage to meet their social, informational, and emotional needs. With platforms like Facebook, Instagram, and TikTok attracting billions of active users, short videos and lifestyle content have become dominant forms of engagement, particularly among Generation Z, who are digital natives with an essential reliance on technology and the internet. Platforms such as Facebook, Instagram, and TikTok, which attract billions of active users, have popularised short videos and lifestyle content as dominant forms of interaction. The aim of this research is to examine the impact of motivational quotes on Generation Z, focusing on their engagement patterns and preferences for specific types of quotes. This quantitative survey research results reveal that social media, especially Instagram and TikTok, serve as primary channels for motivational content consumption. A notable gender difference was found in engagement, with females showing a higher participation rate in motivational content, suggesting the need for targeted strategies for content creators. The findings indicate that motivational content on social media is a valuable tool for fostering emotional support and resilience. Future research should examine this gap in greater depth, exploring the long-term effects of motivational content on mental health, its potential over-reliance, and its impact across different cultural contexts and demographics within Malaysia.